The Student Learning Activity Levels on the Online Learning During the Covid-19 Pandemic - Bahar Agus Setiawan; Sofyan Rofi; Tri Endang Jatmikowati (Program Pascasarjana Universitas Ibrahimy, 2021)
Online learning is a problem solving during the Covid-19 pandemic. Al-Amin Muhammadaiyah Boarding School (MBS) of Bojonegoro as one of the educational institutions under the auspices of Muhammadiyah is consistent and obedient to the decision of both central and regional governments to eliminate offline learning as an effort to reduce the spread of the Covid-19 virus. The implementation of online learning at Al-Amin MBS of Bojonegoro uses google classroom, zoom metting and whatssapp application. The effectiveness and efficiency of online learning can be linked to the level of student learning activities related to attendance, doing assignments, discussions and others. The formulation of this research problem is How is the level of learning activity of Al-Amin MBS of Bojonegoro students in online learning during the Covid-19 pandemic? The purpose of this study was to determine the level of student learning activity and the treatment strategies or treatment of Al-Amin MBS in the implementation of online learning. This study uses a qualitative approach with survey research type. The data analysis used quantitative descriptive method. The results showed that the level of student learning activity was in the active or good category. The treatment strategies or treatments prepared by Al-Amin MBS of Bojonegoro in online learning are reducing the duration of lesson time and requiring teachers to make a resume of each learning material.